2021
DOI: 10.3389/fcimb.2021.632679
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Rapid and Simplified Protocol for Direct Identification of Microorganisms From Positive Blood Cultures by Using Matrix Assisted Laser Desorption Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS)

Abstract: Early and rapid identification of microorganisms is critical for reducing the mortality rate caused by bloodstream infections (BSIs). The accuracy and feasibility of directly identifying pathogens in positive blood cultures by matrix assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) has been intensely confirmed. In this study, we combined density centrifugation and extra chemical lysis-extraction to develop an optimized method in the blood culture process, which significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The use of MALDI-TOF MS is a major innovation in microbial identification. 32 After BCs are treated with specific methods, pathogenic bacteria can be rapidly identified directly with MALDI-TOF MS. 10 , 33 , 34 Pan et al used a lysis–centrifugation–wash procedure to prepare microorganisms from positive BCs, and then directly identified them with MALDI-TOF MS, with 96.49% accuracy, consistent with our results. 35 However, not all microbiology laboratories have access to MALDI-TOF MS for bacterial identification, and must identify bacteria with conventional biochemical-reaction-based instruments.…”
Section: Discussionsupporting
confidence: 88%
“…The use of MALDI-TOF MS is a major innovation in microbial identification. 32 After BCs are treated with specific methods, pathogenic bacteria can be rapidly identified directly with MALDI-TOF MS. 10 , 33 , 34 Pan et al used a lysis–centrifugation–wash procedure to prepare microorganisms from positive BCs, and then directly identified them with MALDI-TOF MS, with 96.49% accuracy, consistent with our results. 35 However, not all microbiology laboratories have access to MALDI-TOF MS for bacterial identification, and must identify bacteria with conventional biochemical-reaction-based instruments.…”
Section: Discussionsupporting
confidence: 88%
“…Bacillus bacteria can be lethal pathogens used as biological weapons, cause opportunistic infections, contaminate food, and be used as probiotics. , In addition, Bacillus species can produce a variety of extracellular enzymes such as amylase, protease, lipase, and lecithinase, so they can potentially grow and spoil a variety of food matrices. , Reference spectra of many Bacillus species are available in commercially available databases such as Biotyper 3.0; however, due to the presence of endospores that mix with vegetative cells, the classification and identification of spore-forming bacterial strains using MALDI-TOF MS is complicated. It was demonstrated that the variable vegetative-endospore composition of bacterial cells has a direct impact on the identification of bacteria and that the proportion of SASP ranging from 8 to 20% is inconsistent, making accurate identification of bacteria of the Bacillus species even more difficult. …”
Section: Discussionmentioning
confidence: 99%
“…Thanks to the use of FA instead of TFA (protocol two), the identification of Gram-positive bacteria increased to 67% and remained high for Gram-negative bacteria (88%). The latest research by Dai et al describes a fast and simplified protocol to identify microorganisms directly from blood cultures on the basis of the addition of the Triton X-100 reagent and centrifugation [ 99 ]. The results of the research show that a high level of identification was achieved for Enterobacterales (96.81%), Enterococcus (92.31%), non-fermenting Bacilli (89.07%), and Staphylococcus (88.91%) within 20 min.…”
Section: Bacteria Identificationmentioning
confidence: 99%